2019
DOI: 10.1007/s11145-019-09957-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a refined model of home literacy activities and associations with children’s emergent literacy skills

Abstract: Based on the Home Literacy Model, this study explored a refined model of home literacy activities and their relations with children's emergent literacy skills in a linguistic and socioeconomic diverse sample of 214 Dutch kindergartners (mean age 4 years and 7 months, 46% girls and 29% monolingual speakers of Dutch). The study examined a typology of home literacy activities that explicitly addressed didactic approach and was not restricted to activities involving print. Next, the study explored the relations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 54 publications
(120 reference statements)
0
39
1
4
Order By: Relevance
“…Martini & Sénéchal, 2012;Sénéchal, 2006;Sénéchal & LeFevre, 2002, 2014. Krijnen et al (2020) expanded the work by Sénéchal and colleagues and showed that parents not only perform direct teaching activities centered around letters and print but also direct teaching activities concerning oral language, such as the teaching of new words and definitions.…”
Section: Measuring Parental Literacy Beliefs: Beyond Shared Reading Bmentioning
confidence: 85%
See 4 more Smart Citations
“…Martini & Sénéchal, 2012;Sénéchal, 2006;Sénéchal & LeFevre, 2002, 2014. Krijnen et al (2020) expanded the work by Sénéchal and colleagues and showed that parents not only perform direct teaching activities centered around letters and print but also direct teaching activities concerning oral language, such as the teaching of new words and definitions.…”
Section: Measuring Parental Literacy Beliefs: Beyond Shared Reading Bmentioning
confidence: 85%
“…Numerous studies into the HLEs of families from various backgrounds have shown that parents involve their children in a multitude of activities which may contribute to children's literacy development. Families may engage their children in a wide array of oral language activities that support literacy-related skills, such as singing songs, storytelling, and mealtime conversations Krijnen, Van Steensel, Meeuwisse, Jongerling, & Severiens, 2020;Van Steensel, 2006;Weigel et al, 2006). Additionally, families carry out informal print-related activities other than shared reading, such as playing letter games and discussing bible texts (Purcell-Gates, 1996).…”
Section: Measuring Parental Literacy Beliefs: Beyond Shared Reading Bmentioning
confidence: 99%
See 3 more Smart Citations